Engaging toddlers in interactions during meals: group-related joint attention - Os, Ellen (Nordisk barnehageforskning, 2019)
Knowledge on how caregivers engage and interact with groups of toddlers in childcare settings is limited. Practice in toddler care is often based on individual approaches even though childcare is a group setting. This study focused on how caregivers created joint attention with toddlers in 12 groups during mealtimes. The results showed that some caregivers took the lead and engaged their groups in sustained joint attention episodes. The children in these groups seemed to be engaged in interactions that involved multiple children and had a rich variety of content. Other caregivers seemed unengaged, and their groups had few, brief interactions that mostly did not meet the criteria for joint attention. In these groups, the interactions largely consisted of rules and regulations.